The potential of kaolin as a reinforcing filler for rubber composites with new sulfur cure systems. (August 2017) - Sheikh, Saad H; Yin, Xuena; Ansarifar, Ali; Yendall, Keith
The effect of a large amount of kaolin (China clay) on the viscosity, cure, hardness, Young's modulus, tensile strength, elongation at break, stored energy density at break, tear energy and compression set resistance of some sulfur-cured natural rubber, polybutadiene rubber and ethylene-propylene-diene rubber composites was investigated. The kaolin surface had been pre-treated with 3-mercaptopropyltrimethoxysilane to improve its dispersion in the rubbers. For natural rubber, the hardness and Young's modulus improved, tensile strength and tear energy were unchanged and the remaining properties deteriorated when kaolin was added. The viscosity increased and the scorch and optimum cure times decreased whilst the cure rate rose with kaolin. For polybutadiene rubber and ethylene-propylene-diene rubber, with the exception of the compression set resistance, all the properties including the viscosity gained from the kaolin. The kaolin was found to be extending or non-reinforcing filler for natural rubber, and highly reinforcing for polybutadiene rubber and EPDM. In addition, the scorch and optimum cure times and cure rate of polybutadiene rubber benefitted, whereas with the exception of the scorch time, the optimum cure time and cure rate of ethylene-propylene-diene rubber were adversely affected by kaolin.